Does precipitation pattern foretell Gujarat climate becoming arid ? (MAUSAM, 1979)
In recent years, on account of the anomalous behavior of southwest monsoon, drought conditions Das were reported from many parts of the country, Gujarat State in particular. An attempt has been made in this paper  to determine, if Gujarat is turning drier.Southwest monsoon (seasonal) and the annual rainfall series of nearly 70 years were subjected to sophisticated statistical analyses. Rainfall data over Gujarat was found to constitute a random series and did not exhibit presence of trend, cycle or persistence. The precipitation pattern does not indicate that arid conditions are gradually increasing over Gujarat State. It is also not feasible to anticipate years of poor rainfall from the past occurrences series.